El régimen impositivo simplificado ecuatoriano y la cultura tributaria del sector de la economía informal de la ciudad de Latacunga en el período 2010-2011. - Barbosa Reyes, Mónica Jeaneth (2015)
This work has been performed for the general public and especially informal traders adopt a Tax Culture whose purpose is to fulfill its obligations to the State; for which it has made the diagnosis and analysis of this issue. The taxpayers ignorance about the benefits that the RISE system gives has caused not comply with the laws established by the treasury. For this reason, the research has raised the following main categories which are synthetized in two variables; the first one is the Economy and Taxation where the economic environment is described, the informal economy, tax system, the Internal Revenue Service and the Simplified Tax System, and the second one is the Tax Culture regarding to accountability, the social sector, National Plan for Good Living and the actual Tax Culture itself that allowed them to give a clear idea about the obligations and responsibilities of taxpayers and the social responsibility of the government to the people. The methodology used was descriptive because there is no manipulation of variables, but just watched as presented, the unit of study was determined from the information gathered by the Municipal GAD of Latacunga, where the survey was administered to a sample traders and interview the Provincial Director of SRI was performed to determine the needs of the population and raise the solution. The stated hypotheses were "More than 50% of informal traders do not know about the taxation through the Simplified Tax System" and "Over 65% of informal traders, support a tax plan training related to RISE system". To test these hypotheses we have considered the questions No. 7 and 8 respectively, and questions 7 and 9 from the interview. Once the data were analyzed and interpreted to determine the conclusions and recommendations, where a training plan was stated for this vulnerable sector of society which has four seminars workshop consisting of thematic aims and strategies to be used.